Marriage Simulation as an Innovative Method to Understand Munaqahat Fiqh in Higher Education - Anton; Fiqra Muhamad Nazib; Anita Hasanah (al-Afkar, Journal For Islamic Studies, 2025)
This study explores the application of marriage simulation as an innovative method for understanding fiqh munaqahat in higher education, specifically in Islamic Education programs. Fiqh munaqahat, which deals with marriage, divorce, and the rights and duties of spouses according to Islamic law, often presents challenges for students who struggle to connect theoretical knowledge to practical life situations. The marriage simulation offers a solution by allowing students to actively engage in all stages of the marriage process, from the akad nikah (marriage contract) to the ceremonial hajatan (wedding reception), applying Islamic principles in a real-world context. This hands-on experience enriches students’ understanding of the complexities of marital life, enhances their practical skills, and prepares them for the future responsibilities of marriage, making the learning process more applicable and engaging. The study emphasizes the benefits of this method, not only in deepening theoretical knowledge but also in providing crucial emotional and social skills necessary for successful relationships.